Bullying di Sekolah: Analisis Penyebab dan Strategi Guru PAI dalam Penanganannya - Masrur; Indra Permadi; Mahfud Junaedi (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
Bullying cases often occur in schools and in the community, so this needs to be handled so that it does not continue. The role of Islamic religious education and teachers' efforts is crucial in dealing with bullying using an Islamic values ​​approach, therefore this research aims to analyze PAI teachers' efforts in preventing bullying using an Islamic values ​​approach. This research uses library research. The collection technique collects relevant studies from various scientific articles, books, and reading sources relevant to the topic. The theories obtained were studied practically and presented in this article. This study presents an analysis of the causes of bullying, the role of Islamic religious education teachers, and efforts to play the role of Islamic religious education as a basis for preventing bullying.